MACROPHAGE ACTIVATION SYNDROME IN PATIENTS WITH SYSTEMIC JUVENILE ARTHRITIS - S. R. Rodionovskaya; I. P. Nikishina (Научно-практическая ревматология, 2014)
Macrophage activation syndrome (MAS) is one of the histiocytic diseases developing from cells of a macrophage series, hemophagocytic lymphohis- tiocytosis (HLH). Rheumatic diseases have been demonstrated to be often associated with the development of SAM, most often upon systemic juve- nile arthritis (SJA). Certain issues have been discussed concerning pathogenesis with the concept of the defect of mechanisms of T-cell cytotoxicity and a reduction of the activity level of natural killer (NK) cells, which are associated with a mutation in the PRF1 gene encoding perforin, as well as the overproduction, by T-lymphocytes and histiocytes, of the number of cytokines (interleukin 1β – IL1β, interferon γ, the tumor necrosis factor α, the soluble IL2-receptor), which indirectly lead to activation of tissue macrophages and production of proinflammatory cytokines. The diagnosis problems associated with the low sensitivity and specificity of the HLH 2010 diagnostic criteria for hemophagocytic syndrome, which are based on the molecular genetics and pathomorphological diagnosis of HLH, are discussed. The diagnostic criteria for macrophage activation syndrome (2012) developed for SJA are presented. Thrombocytopenia, hyperferritinemia, and pathohistological signs of hemophagocytosis are of greatest significance. Attention is paid to the need for the diagnosis of subclinical and mild forms of SAM, to identification of the potential risk groups, and prevention of SAM development. The problems of differential diagnosis are considered with allowance for the similarity of clinical manifestations with SJA, treat- ment tactics using the HLH 2004 protocol, and biological therapy.